Papuri at pagsamba sa wikang Pilipino - Endab, Jeremiah Paul B. (2014)
"This study aims to develop a set of new praise and worship songs in the Filipino language".
Thesis (B.M. Music Education) -- University of the Philippines Diliman.
Keywords: Spiritual songs